Analysis of the Social Development Program: Smart Kampung Program of Banyuwangi Regency: Analisa Program Pembangunan Sosial : Smart Kampung Kabupaten Banyuwangi - Alfian Mahendra; Moch. Ilham Noer Sunan; Riska Nur Azizah; Shofira Nur Aliya P; C Aliffiana Fadhilah Jasmine; Falka Patria Senoaji (Universitas Indo Global Mandiri, 2026)
Purpose : This study examines the Smart Kampung Program in Banyuwangi Regency through Midgley’s social development framework, with particular attention to the integration of individual, community, and governmental roles in enhancing rural social welfare. Design/methodology/approach : Employing a descriptive qualitative approach with a case study design, the research is based on a systematic literature analysis of peer-reviewed journals, official government reports, regional regulations, institutional publications, and other credible online sources. Data were analyzed using the interactive model proposed (Miles dkk., 2014), encompassing data reduction, data display, and conclusion drawing and verification. Findings : The findings reveal that the Smart Kampung Program has effectively combined technological innovation, governance reform, and community empowerment to improve public service delivery and citizen participation. Nevertheless, the integration among key actors remains uneven, particularly with regard to social sustainability and disparities in human resource capacities across villages. Practical Implication : The study offers practical implications for local governments and policymakers in strengthening inclusive and sustainable rural development models grounded in social development principles. Originality/value : The originality of this research lies in its application of Midgley’s theoretical framework to analysis of the Smart Kampung Program, thereby contributing a novelty perspective to the discourse about social development on village level.